Eficácia terapêutica de RNAs de interferência (siRNAS) e avaliação da resposta imune em camundongos infectados com vírus da raiva de origem de cão e de morcego - Appolinario Harary, Camila Michele [UNESP] (2014)
Rabies is a lethal infectious disease that kills more than 55 thousand persons per year worldwide although death can be avoided if a post-exposure prophylaxis based in anti-rabies vaccine and immune globulins can be applied on time. After the onset of clinical signs, there is no effective therapy available. Cytokines and chemokines are crucial for host immune response development. This study had as purpose to evaluate the gene expression of cytokines and chemokynes related to the immune response and also to evaluate the efficacy of siRNAs therapy in mice inoculated with dog or bat virus. Results demonstrated that the gene expression profile was intrinsic to virus variant and the precocious production seemed to be more important than their expression levels for rabies survival. Therapy with siRNAs therapy showed no difference in the lethality rate between treated groups and controls but clinical evaluation of animals inoculated with dog variant showed less severity of clinical disease in the treated group compared with control, also associated with a low expression of N gene and of all immune markers evaluated at 5 days. Results provided some evidence of the efficacy of siRNAs therapy in infections due to dog variant but not due to bat variant in the present study